1987
DOI: 10.1254/jjp.45.125
|View full text |Cite
|
Sign up to set email alerts
|

Positive inotropic action of .KAPPA. opiate agonists, ethylketocyclazocine and dynorphin-A(1-13), in isolated rat atrium.

Abstract: Abstract-The effect of various opiate agonists on the contraction of isolated rat atrium was investigated. Ethyl ketocyclazocine (EKC) (30-100 ,uM) and dynor phin-A(1-13) (10-30 uM), which are ic-type agonists, caused positive inotropic effects on electrically stimulated left atrium in a dose-dependent manner. In addition, EKC decreased the frequency of spontaneous beating in the right atrium. Morphine (fl-type), [Met5] and [Leu5]-enkephalin (O'-type) did not affect both the developed tension and frequency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Gautret and Schmitt (1985) showed that dynorphin produced bradycardia in pentobarbital-anesthetized rats, even following bilateral vagotomy, suggesting a direct action on the heart. Further support for a direct inhibitory action of kappa agonists on the heart comes from a study by Maeda et al (1987), who showed a decrease in beat frequency in the isolated rat atrium following treatment with EKC and dynorphin. In this study, the kappa agonists did produce a positive inotropic effect, indicating that kappa agonists can have some excitatory effects in the periphery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gautret and Schmitt (1985) showed that dynorphin produced bradycardia in pentobarbital-anesthetized rats, even following bilateral vagotomy, suggesting a direct action on the heart. Further support for a direct inhibitory action of kappa agonists on the heart comes from a study by Maeda et al (1987), who showed a decrease in beat frequency in the isolated rat atrium following treatment with EKC and dynorphin. In this study, the kappa agonists did produce a positive inotropic effect, indicating that kappa agonists can have some excitatory effects in the periphery.…”
Section: Discussionmentioning
confidence: 99%
“…With any pharmacological treatment for drug abuse, it is inevitable that the treatment drug and the abused drug will be used in combination in some individuals that relapse to drug use. While a number of studies have looked at the effects of kappa agonists on cardiovascular function, most of these studies have been performed in isolated organ preparations (e.g., Kannan and Seip, 1986;Maeda et al, 1987;Wong et al, 1990) or anesthetized animals (Laurent and Schmitt, 1983;Punnen and Sapru, 1986;Rochford et al, 1991). The purpose of this study was to determine the cardiovascular effects of two representative kappa opioid agonists in a conscious, non-human primate model of cardiovascular function.…”
Section: Introductionmentioning
confidence: 99%